Transformable Spinose Nanodrums with Self‐Supplied H2O2 for Photothermal and Cascade Catalytic Therapy of Tumor. Issue 7 (26th May 2021) - Liu, Miao‐Deng; Guo, Deng‐Ke; Zeng, Run‐Yao; Guo, Wen‐Hui; Ding, Xing‐Lan; Li, Chu‐Xin; Chen, Ying; Sun, Yunxia; Zhang, Xian‐Zheng
Abstract: Advances in enzymes involve an efficient biocatalytic process, which has demonstrated great potential in biomedical applications. However, designing a functional carrier for enzymes equipped with satisfactory degradability and loading efficiency, remains a challenge. Here, based on transformable liquid metal (LM), a spinose nanodrum is designed as protein carrier to deliver enzyme for tumor treatment. With the assistance of spines and a special drum‐like shape, it is found that the spiny LM can carry much more enzymes than spherical LM under the same condition. Benefiting from the satisfactory enzyme loading efficiency of spiny LM, a plasma amine oxidase immobilized spinose LM nanosystem enveloped with epigallocatechin gallate (EGCG)‐Fe 3+ (LMPE) is fabricated for photothermal and cascade catalytic tumor therapy. Activated by the acidic condition in the tumor microenvironment, the LMPE can oxidize spermine (Spm) and spermidine (Spd) to generate hydrogen peroxide (H2 O2 ) for Fenton catalytic reaction to produce the lethal hydroxyl radical (OH) for tumor cell killing. Combined with remarkable photothermal performance of LM, LMPE exhibits significant inhibition of tumor in vivo. Abstract : An enzyme‐loaded spinose liquid metal (LM) system is fabricated for photothermal and enhanced catalytic therapy. Benefiting from the satisfactory enzyme loading performance of the spinose LM, the system can achieve the cascade catalytic therapy of polyamines oxidation and Fenton catalytic reaction for the effective inhibition of tumor growth in vivo.